First representatives of the stonefly genus Perlomyia and the beaded lacewing genus Isoscelipteron from the Upper Miocene of France (Plecoptera: Leuctridae and Neuroptera: Berothidae), with biogeographical considerations - Boderau, Mathieu; Ngo-Muller, Valerie; Nel, André (Zootaxa, 2024)
The leuctrid stonefly Perlomyia cantalensis sp. nov. and the berothid lacewing Isoscelipteron bertrandi sp. nov. are described from the Upper Miocene (ca. 5.60 ± 0.3 Ma) Konservat-Laggerstätte of Sainte-Reine (Cantal, France). They represent the first fossil representatives of their respective genera. Perlomyia Banks, 1906 is currently distributed in the Eastern Palearctic and the Western Nearctic coasts and islands. All extant Perlomyia spp. are known to live in streams, rivers and creeks, suggesting the presence of rivers connected to the maar paleolake of Sainte-Reine. The genus Perlomyia was much more widely distributed during the Miocene than today and probably disappeared in Europe due to the Quaternary glaciations. The genus Isoscelipteron Costa, 1863 is currently distributed in the Nearctic, Eastern Palaearctic, Indomalaysia, and Australasia regions, together with two relictual Mediterranean species. These two examples show that the study of the entomofauna from the diatomite outcrops of the Miocene of center of France helps to calibrate the history and origin of modern Palearctic insects.